Visualisasi Data Pasien Rawat Jalan di RS. Mitra Keluarga Bekasi Timur dengan Teknik Business Intelligence - Sakalessy, Wiliam Fredrick; Samosir, Ridha Sefina (Research and Community Service UNIVERSITAS KALBIS, 2025)
Mitra Keluarga Hospital Bekasi Timur is a private hospital that committed to providing the best health service for families in Indonesia. Currently this hospital has problems in the outpatient service section in terms of service time that is not in accordance with hospital standards. The purpose of this study is to visualize outpatient data using business intelligence techniques in the form of a dashboard so that it can help hospitals solve problems if there are discrepancies in service time. Use business intelligence methods by using Microsoft Power BI tools to assist the analysis process with multiple charts such as bar charts, line charts, and pie charts. The result of this research is a dashboard that helps the hospital management to integrate information from each visualization of the number of patients and the time of outpatient services.